Prototype of a 3D printing scrap recycling machine - Rosdi, Raziq Amir; Rusli, Ahmad Najmie (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project presents a prototype of a 3D printing scrap recycling machine, designed to process and reduce waste from failed or excess PLA prints. The structure of the prototype is constructed primarily from acrylic and wood, providing a lightweight yet stable frame for demonstration purposes. The core component of the machine is a shredder unit made from solid mild steel cylinders, featuring a three layers shredder system. Each layer having a different shredder diameter. This design enables the machine to efficiently shred large 3D printed parts up to 50mm x 50mm in size. The output from the shredder consists of coarse PLA debris, which can then be further processed into finer particles using an external blender machine for filament re-extrusion or other recycling processes. The system is powered by a 12V DC motor, with power transmission to the shredder layers achieved via a gear and chain mechanism ensuring synchronized and efficient operation across all layers. This prototype demonstrates a scalable and low cost solution for reducing 3D printing waste in small scale or desktop 3D printer.